2019
DOI: 10.1080/24750263.2019.1695967
|View full text |Cite
|
Sign up to set email alerts
|

Transposable elements in vertebrates: species evolution and environmental adaptation

Abstract: The evolutionary success of species is strictly related to their genome in terms of composition and functionality. Transposable elements (TEs) represent a considerable fraction of the nuclear DNA content, and given to their ability to spread throughout the genome, they are able to create genetic diversity at sequence, gene structure, and chromosome level. Vertebrates represent a highly successful taxon and its lineages are characterized by a variable TE content suggesting a different impact on the genome. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…However, the host’s silencing mechanisms are not always effective, and the evolutionary success of TEs is undeniable. They are ubiquitous and account for a large fraction of eukaryotic genomes; they have driven many key evolutionary innovations and resulted in genetic diversity and evolutionary success [ 51 , 58 ]. They have even been suggested to play a possible role in speciation [ 59 ].…”
Section: Transposable Elements Exaptation and Human Evolutionmentioning
confidence: 99%
“…However, the host’s silencing mechanisms are not always effective, and the evolutionary success of TEs is undeniable. They are ubiquitous and account for a large fraction of eukaryotic genomes; they have driven many key evolutionary innovations and resulted in genetic diversity and evolutionary success [ 51 , 58 ]. They have even been suggested to play a possible role in speciation [ 59 ].…”
Section: Transposable Elements Exaptation and Human Evolutionmentioning
confidence: 99%
“…Genetic variation can be caused by not only point mutations and whole-genome duplications but also TE activity. Moreover, transposons can be co-opted and exapted, creating regulatory sequences, coding exons, or entirely new genes useful for the host genome [ 22 , 23 , 37 , 205 ]. Indeed, a great number of reports have suggested the responsiveness and susceptibility of TEs to environmental changes or stressful conditions [ 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 ].…”
Section: Fish Transposons and The Environmentmentioning
confidence: 99%
“…Finally, the presence of mobile elements in fish genomes most likely contribute to shaping their genomes, providing advantageous features that have allowed them to successfully adapt to different environments [ 21 , 22 , 23 ]. Given the ability to move throughout the genome, the impact of mobile elements on genome evolution is higher than commonly supposed, and several papers have recognized the role of these elements as one of the most powerful evolutionary tools [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researches on transposons have shown that they are among the main causes of genome expansion and that their activity is stimulated by various environmental stressors (Canapa et al 2015;Carducci et al 2019b), such as temperature, thermal shocks, radiations, chemicals, and viral infections (Capy et al 2000;Fujino et al 2011;Garcia Guerreiro 2012;Carducci et al 2019a, b). In some cases, these stressors would act directly on transposons with a mechanism typical of defensive gene activation, since some transposons have sequences similar to the promoters of these genes (Takeda et al 1999;Capy et al 2000); however, in many other cases, the action would mainly depend on a temperature-dependent activation of transposase (Capy et al 2000;Fujino et al 2011;Carducci et al 2019a).…”
Section: Relationship Of Genome Characters With the Environmentmentioning
confidence: 99%